Footloose (1984) [videorecording (DVD)] - Ross, Herbert, 1927-2001; Bacon, Kevin, 1958-; Penn, Christopher; Wiest, Dianne; Singer, Lori, 1957-; Lithgow, John, 1945-; Parker, Sarah Jessica (Paramount Home Entertainment, 2011)
This is the original film starring Kevin Bacon. When city-boy Ren McCormick finds himself in an uptight Midwestern town where dancing has been banned, he revolts with best friend Willard and the minister's daughter to change everyone's mind.